(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The analysis of the consequences of the COVID-19 pandemic on the cultural rights of national minorities in the countries of Central Eastern, Baltic and Balkan Europe (CEBBE) cannot ignore the fact that since the end of the 1980s, the forms of State of these countries – “inspired”, albeit in different measures, by the Socialist one – have been affected by a number of changes, which in turn influenced their models of minority protection. The article therefore pays particular attention to the relationship between the evolution of the forms of States in CEBBE countries and the shaping of new models of protection of cultural rights of minority groups. This analysis is functional not only to identify in a comparative perspective similarities and differences between the models of protection of minority cultural rights, but above all to verify the effective guarantee of the same in the context of the democratic backsliding experienced by some CEBBE countries, further exacerbated by the COVID-19 pandemic.